Diversity and abundance of ants (Hymenoptera: Formicidae) as indicators of sugarcane agroecosystem stability in Blitar, East Java, Indonesia - SUJAK SUJAK; BAMBANG TRI RAHARDJO; FAIZ NASHIRUDDIN MUHAMMAD; AKHMAD RIZALI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sujak, Rahardjo BT, Muhammad FN, Rizali A. 2023. Diversity and abundance of ants (Hymenoptera: Formicidae) as indicators of sugarcane agroecosystem stability in Blitar, East Java, Indonesia. Biodiversitas 24: 5336-5342. The abundance of ant communities can be used as an indicator of stability in agroecosystems. This study was designed to evaluate the diversity and abundance of ant in three sugarcane cultivation ecosystems. The research was conducted in Ngembul Village, Binangun Subdistrict, Blitar, East Java, Indonesia from August 2021 to February 2022 The three observed sugarcane ecosystems were Ratoon Cane (RC) without tillage, Replanting Ratoon Cane (PRC) with tillage, and Newly Cultivated Plant Cane (NPC) with tillage. Ant collections were made using the pitfall trap method. In each field, pitfalls were systematically placed at 5 points. Pitfall traps were set for 24 hours, and samples were collected every 2 weeks. Identification was done at the genus level and further separated based on morphology (morphospecies). The research obtained 2,920 ant individuals belonging to 3 subfamilies, 7 genera, and 9 morphospecies. The highest diversity and abundance were found in the RC ecosystem compared to the PRC ecosystem and the NPC agroecosystem. The most dominant ant species was Crematogaster sp.1. The ant population in the RC ecosystem has more population growth compared to the PRC and NPC ecosystems. The results of the ANOSIM analysis indicated differences in ant community composition among the treatments. In conclusion, the ratoon sugarcane ecosystem sustains diversity and abundance of ants more compared to the other two ecosystems.